PENGARUH PERLAKUAN ALKALI TERHADAP SIFAT TARIK SERAT EMPULUR SAGU UNTUK APLIKASI PEMBUATAN KOMPOSIT BERBASIS SERAT ALAM - Graciadiana. I. Huka; Leslie. S. Loppies (Journal Mechanical Engineering, 2023)
This study aimed to observe the changes in tensile properties of sago pith fiber which has been given the alkali treatment 5% NaOH with the variation of time 0,30,90,120,150,180,210,240 minutes. The object of this study is sago pith fiber. These fibers are cleaned with 100 mm length, the fibers were treated alkali 5% NaOH and tested by using IMADA tensile machine test.The final results this study is shown in relationship between tensile propesties (strength, modulus and strain) versus time of alkali treatment. Based on the test results were obtained the maximum tensile strength of lontar midrib fiber at alkali treatment 240 minutes (4 hours) and maximum modulus of elasticity in the alkali treatment 240 minutes (4 hours). Tensile strength and modulus elastistacity of treated sago pith fiber in comparison with pure sago pith fibers have increased tensile strength and modulus of elasticity is highly significant to 273,15 % dan 122,7%.Keywords : Mechanical Property, sago pith fibers, composite